Employee Performance Determinants Through Communication Professionalism and Job Satisfaction: Faktor-Faktor Penentu Kinerja Karyawan Melalui Profesionalisme Komunikasi dan Kepuasan Kerja - Hasan Ubaidillah; Muhammad Naufal (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Human resource management emphasizes employee performance as a central driver of organizational productivity. Specific Background Performance issues were observed at the Surabaya branch where internal evaluations showed declining scores, highlighting the relevance of interpersonal communication, professionalism, and job satisfaction as workplace determinants. Knowledge Gap Prior studies often examined these factors separately, while integrated empirical evidence within one organizational setting remained limited. Aims This study examines the relationships of interpersonal communication, professionalism, and job satisfaction with employee performance. Results Using a quantitative explanatory design with 109 randomly selected employees, questionnaire data analyzed through multiple linear regression indicate that each variable shows significant partial associations and jointly contributes to performance, with professionalism displaying the strongest coefficient. Novelty The study offers a simultaneous model combining three behavioral and managerial constructs within a single public utility organization. Implications Findings provide managerial guidance for strengthening internal communication practices, reinforcing professional conduct, and maintaining employee satisfaction to support consistent work outcomes and organizational productivity. Keywords: Interpersonal Communication, Professionalism, Job Satisfaction, Employee Performance, Human Resource Management Key Findings Highlights: Professional conduct shows the highest regression coefficient among predictors Open interaction among staff aligns with better work results Fair compensation relates to stronger task completion levels